Morphology of Stomach of Indian Spotted Chevrotain (Moschiola indica) - Rajani, C. V.; Surjith, K. P.; Patki, H. S.; Simanta; Raghu, P.; N. K.; Raj, Indu V; Pradeep, M.; Maya, S. (Indian Journal of Veterinary Anatomy, 2023)
Chevrotain, an even-toed ungulate belonging to the genus Tragulus, is classified under the family Tragulidae and the suborder Ruminantia. Indian spotted Chevrotain has a narrow head, pointed muzzle, and olive brown hair coat with pale or white spots or stripes on the dorsum. The present study was done to study the typical morphological features of the stomach in Indian spotted Chevrotain. The material for the work was collected from four numbers of adult Indian spotted Chevrotain when the animals were presented for post-mortem examination. The large compound stomach presented clearly demarcated, well-developed rumen, reticulum, abomasum, and a primitive, less clearly demarcated omasum. Rumen was the largest compartment and the grooves demarcated it in to a dorsal sac, a ventral sac, and a caudo-ventral blind sac. Left dorsal accessory groove and caudodorsal blind sacs were absent. Rumen morphologically resembled "three quarter- S shape."The interior of the rumen showed typical pillars corresponding to the groves. Ruminal papillae were evenly distributed in the various compartments including the pillars. The second largest compartment, reticulum, was much larger than omasum and larger than abomasum. The ruminal and reticular portion of the rumino-reticular pillar presented fine ruminal papillae. The "honey-comb" cells were shallow and were not subdivided. Omasum constituted the smallest compartment. It was like a small dorsal dilatation cranial to the abomasum. Though it was not clearly distinct externally, internally it presented prominent omasal folds. The elongated abomasum had a fundus, a body, and a pyloric part. Its fundus contacted the abdominal floor; and following an acute angle at the body, the pyloric part coursed caudo-dorsally.